Digest: How do nonnative frugivorous birds adapt to life in O'ahu?*. (3rd June 2019) - Isaacson, Joshua
Abstract: Species adapt to the selective pressures of novel environments. Here, Gleditsch and Sperry tested whether four nonnative frugivorous bird species on the Hawaiian island of O'ahu diverged morphologically from their ancestral populations. They found that all four species significantly diverged from populations in their native ranges, with a general trend of smaller body size and larger bills. These differences were likely due to a combination of adaptive and nonadaptive processes.